1989
DOI: 10.1017/s0022149x00008671
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of migrating Ascaris larvae and Escherichia coli in piglets

Abstract: The effect of intestinal flora on the establishment, development and pathogenicity of Ascaris suum larvae in piglets (Large White breed) was investigated. The infected piglets with Ascaris and Escherichia coli showed signs of pneumonia, cough with respiratory difficulties initially even though these moderated with time. They lost appetite and showed signs of unthriftiness with loss of weight. The packed cell volume was normal but the differential leucocyte counts of the pigs infected with Ascaris larvae and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Increased susceptibility to bacterial infections including Pasteurella multocida, Escherichia coli and Salmonella spp. and reduced bacterial clearing from the lung has previously been associated with ascariasis (Adedeji et al, 1989;Curtis et al, 1987;Smith et al, 2011;Tjornehoj et al, 1992). On the other hand, A. suum infection also reduces the efficacy of the immune response after vaccination (Steenhard et al, 2009;Urban et al, 2007).…”
Section: Tablementioning
confidence: 96%
“…Increased susceptibility to bacterial infections including Pasteurella multocida, Escherichia coli and Salmonella spp. and reduced bacterial clearing from the lung has previously been associated with ascariasis (Adedeji et al, 1989;Curtis et al, 1987;Smith et al, 2011;Tjornehoj et al, 1992). On the other hand, A. suum infection also reduces the efficacy of the immune response after vaccination (Steenhard et al, 2009;Urban et al, 2007).…”
Section: Tablementioning
confidence: 96%
“…Bottjer et al (1978) reported that the nematode parasite Nematospiroides dubius third stage larvae act as vector for Salmonella enterica serovar Typhimurium in the infection of mice. Nalin and McLaughlin (1976) demonstrated colonisation of Ascaris lumbricoides by Vibrio cholerae, and Adedeji et al (1989) reported a synergistic eect of Ascaris larvae and E. coli in piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the interactions between A. galli and Escherichia coli in chickens have indicated that subclinical A. galli infections, may have an immunosuppressive effect, allowing E. coli to establish itself (Permin et al, 2002). Likewise, a synergistic effect of migrating Ascaris suum larvae and E. coli was observed in piglets (Adedeji et al, 1989) and of salmonellosis on subsequent infections with A. suum in adult swine (Wade and Gaafar, 1981). A similar effect may exist for P. multocida infections in A. galli infected¯ocks.…”
Section: Introductionmentioning
confidence: 83%